Residential Neighborhood Development - Najati, Riyadh Fikret; Abbas, Sanaa Sati (Iraqi Journal of Architecture and Planning, 2019)
development and such as the problem of research, where the goal of the research to build a theoretical framework to fill this gap. The research hypothesis that the development of the residential neighborhood is achieved through (integration of the social, economic and environmental aspects associated with the values and principles of sustainable neighborhood). The research relied on an analytical descriptive method in the description and analysis of selected samples namely , and was the criterion of choice based on principles of sustainable residential neighborhoods in contemporary trends . The research concluded that the residential neighborhood based on the principles of development distinct , by achieving social, economic, environment aspects, as well as the urban design and planning values. The sustainable residential neighborhood pattern emphasizes regional development considerations, and principles that define sustainable features including compactness, mixed use, connectivity, pedestrian oriented built form, , vital public realm, and regulation of the relationship with transit transport.